The Role of Relationship Quality and Loyalty Programs in Building Customer Loyalty in E-Commerce Platforms - Andiyana, Egi (Manunggal Halim Jaya, 2026)
This study the role of relationship quality and loyalty programs in building customer loyalty within Indonesian e-commerce platforms, with supplier preference positioned as a mediating variable. Grounded in relationship marketing theory, this research investigates how trust, satisfaction, and commitment influence customer loyalty both directly and indirectly, while also assessing the moderating role of loyalty programs. A quantitative approach was employed using data collected through an online questionnaire distributed to Generation Z consumers in the Jabodetabek region who had made online purchases within the past month and actively participated in e-commerce loyalty programs. A total of 117 valid responses were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results reveal that relationship quality has a significant positive effect on both supplier preference and customer loyalty. Supplier preference also significantly influences customer loyalty, confirming its role as an important behavioral outcome in e-commerce contexts. In addition, loyalty programs demonstrate significant direct effects on supplier preference and customer loyalty. However, the mediating effect of supplier preference and the moderating role of loyalty programs are not supported. These findings indicate that while transactional incentives remain effective in motivating customer behavior, they do not strengthen the relational mechanisms underlying loyalty formation. This study contributes theoretically by extending relationship marketing literature into digital marketplace settings and practically by offering insights for e-commerce managers in Indonesia to balance relational value and incentive-based strategies. The findings emphasize that sustainable customer loyalty in e-commerce platforms is primarily driven by relationship quality rather than promotional rewards alone.